2021
DOI: 10.1038/s42003-021-02898-1
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure modulates the gut-liver axis in an Alzheimer’s disease mouse model

Abstract: The human Apolipoprotein E4 (ApoE4) variant is the strongest known genetic risk factor for Alzheimer’s disease (AD). Cadmium (Cd) has been shown to impair learning and memory at a greater extent in humanized ApoE4 knock-in (ApoE4-KI) mice as compared to ApoE3 (common allele)-KI mice. Here, we determined how cadmium interacts with ApoE4 gene variants to modify the gut-liver axis. Large intestinal content bacterial 16S rDNA sequencing, serum lipid metabolomics, and hepatic transcriptomics were analyzed in ApoE3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…CAT decomposes hydrogen peroxide, and SOD catalyzes the dismutation of two superoxide radicals degenerate into molecular oxygen in the antioxidant defense system 47 . The up‐regulation of CAT and SOD activities have also been reported in other aquatic organisms after exposures to pesticides, heavy metals, nanoplastics and other contaminants, 48–52 indicating a universal response of aquatic organisms against environmental pollutants.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…CAT decomposes hydrogen peroxide, and SOD catalyzes the dismutation of two superoxide radicals degenerate into molecular oxygen in the antioxidant defense system 47 . The up‐regulation of CAT and SOD activities have also been reported in other aquatic organisms after exposures to pesticides, heavy metals, nanoplastics and other contaminants, 48–52 indicating a universal response of aquatic organisms against environmental pollutants.…”
Section: Discussionmentioning
confidence: 94%
“…62 A previous study reported that cadmium exposure resulted in the hepatotoxicity of mice through the enrichment of the platelet activation pathway. 51 The Rap1 signaling pathway play key roles in signal transduction. 63 Changes in genes expression profiles were also observed in lambs, mice and human corneal epithelial cells under stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[125]. This effect was found along with a reduction in IgG/IgA-producing Bacteroide ovatus (decreased serum IgG/IgA have been found among AD patients) and increases in several pro-inflammatory taxa [126].…”
Section: The Role Of Apoe and Apoe Mimetic Peptides On The Intestinal...mentioning
confidence: 66%
“…After Cd enters the human body, it can cause damage to a series of important organs such as liver, kidney, bone, brain and lung, as well as nervous system, reproductive system, immune system, and other systems, among which liver and kidney are the most important target organs. It is reported that the toxicity of Cd is obviously time-dependent and concentration-dependent ( 74 77 ). The Cd-induced liver injury is mainly due to the competitive replacement of Cd with the metal prosthetic groups in the liver antioxidant enzymes, which inactivates the antioxidant enzymes and reduces the scavenging ability of free radicals, thereby causing cellular lipid peroxidation and oxidative stress ( 78 , 79 ).…”
Section: The Possible Harm Of CD Exposure To the Bodymentioning
confidence: 99%